Stabilometric assessment of vestibular function in children with a medium otitis - Lozova, Iuliia; Garyuk, Grigoriy; Redka, Iryna; Pochuеva, Tatiana (ScienceRise: Medical Science, 2021)
Otitis media is one of the most common infectious diseases of the middle ear in preschool age, but its relationship with vestibular dysfunction remains controversial. The aim of the study was to carry out a comparative analysis of stabilometric indicators of preschool children with suppurative and non-suppurative otitis media. Materials and methods: 22 children with suppurative otitis media and 22 children with non-suppurative otitis media at the age from 4 to 7 years were examined by the method of static stabilometry on the device “MPFI Stabilograph 1” (LLC "ASTER IT", Kharkov, Ukraine). We took into account the indices of variation and distribution of the center of pressure, spectral and correlation indices of the stabilogram, as well as integral indices of stability (length, velocity and angle of postural oscillations) and the quality of the balance function in two sensory states (open and closed eyes), which were calculated in the software providing StabiliS. Results. In children with non-suppurative otitis media, the coordinates of the center-of-pressure corresponded (7.04 [2.16–10.09]; -1.14 [-28.90–9.11]), and with suppurative otitis media – (7.04 [3.30–16.16]; -13.72 [(-25.17)–(-10.30)]) with closed eyes. The averaged figure of the projection of the center-of-pressure in the test with eyes closed is actually represented by a circle in both groups, but with open eyes it is represented by an ellipse, which, in case of non-suppurative otitis media, is stretched along the sagittal axis, and in case of suppurative otitis media, along the frontal axis. In both sensory states, children with non-suppurative otitis media were characterized by large (p≤0.05) values of KurtosisX, Length and lower (p≤0.05) values of CC0X, Pup2Sigma compared with non-purulent otitis media. Conclusions: In preschool age, suppurative otitis media more significantly disrupts the balance function compared with non-suppurative otitis media, which was manifested by a significant decrease in the stability of the main stance and the predictability of oscillatory movements compared with non-suppurative otitis media